A sustainable solution to soil erosion in Vanuatu - Bumseng, George; Kaoh, Peter (Technical Centre for Agricultural and Rural Cooperation, 2018)
From 2001 to 2018, vetiver grass was utilised across Vanuatu for a number of different purposes. Farm Support Association (FSA) used vetiver grass to control soil erosion on farms and roads and to promote the rehabilitation of degraded land. With the support of partners, such as Clean and Green Farming and the Pacific Island Farmers Organization Network (PIFON), and with the help of local youths, the project successfully repaired the soil in a number of communities across the country.